Peran Media Massa sebagai Sarana Iklan Politik Parpol (Kajian Terhadap Kasus Surya Paloh dan Partai Nasdem) - Ali Mustofa (Interaksi: Jurnal Ilmu Komunikasi, 2013)
Abstract :The use of media is very important in the modern political campaigns and socialization. The mass media is not only an integral part of politics, but it also has a central position in politics, able to put together the reality of the events that happened to be a discourse that has the power of political campaigning. In order to win the competition in the arena of elections, political contestants compete by implementing workable strategies of political communication. In the context of the 2014 elections, the mass media still has an important role in the socialization of the party program and the introduction of political candidates. The role of mass media as recognized by Nasdem, Nasdem therefore continue to use the mass media in political communication strategy of the party to win the election. Keywords: mass media, political advertising, political communication strategies  Abstraksi :Penggunaan media sangatlah penting dalam proses kampanye dan sosialisasi politik modern. Media massa bukan hanya bagian integral dari politik, tetapi juga memiliki posisi yang sentral dalam politik, mampu menyusun realitas dari berbagai peristiwa yang terjadi hingga menjadi wacana yang memiliki kekuatan mengkampanyekan politik. Guna memenangkan kompetisi di ajang pemilu, kontestan parpol bersaing dengan menerapkan strategi komunikasi politik yang jitu. Dalam konteks pemilu 2014, media massa tetap mempunyai peran penting dalam sosialisasi program partai dan pengenalan para caleg parpol. Peran media massa seperti ini diakui oleh Nasdem, karenanya Nasdem tetap menggunakan media massa dalam strategi komunikasi politik partai guna memenangkan pemilu.Kata Kunci: media massa, iklan politik, strategi komunikasi politik